PENGARUH EDUKASI TEKNIK MENYUSUI YANG BENAR TERHADAP PERILAKU MENYUSUI PADA IBU POST PARTUM PRIMIPARA DI WILAYAH KERJA PUSKESMAS JATINEGARA KABUPATEN TEGAL (Nursing Care Journal, 2023)
Correct breastfeeding technique is the mother's way of giving breast milk to the baby with the correct attachment, position and release of the nipple. The goal is to avoid various breastfeeding problems such as sore nipples. So that the correct breastfeeding technique education needs to be known by breastfeeding mothers. This study aims to determine the effect of education on correct breastfeeding techniques on breastfeeding behavior in primiparous post partum mothers in the working area of ​​Jatinegara Health Center, Tegal Regency. This research is quantitative research with pre-experimental design. The number of samples in this study were 32 respondents with a total sampling technique. Inclusion criteria included primiparous mothers 2 hours post partum, direct breastfeeding and pumping. The results showed that the majority of respondents aged 23 years (34.3 %), high school education (56.3%), did not work (56.3%), the description of pre-education behavior was sufficient (59.4%) and post-education was good (59 ,4%). Based on the Wilcoxon test, the research results obtained p value = 0.000 (<0.05), so it can be concluded that there is an effect of education on correct breastfeeding techniques on breastfeeding behavior of primiparous postpartum mothers before and after education on correct breastfeeding techniques. It is hoped that further researchers will observe breastfeeding behavior continuously and the provision of education can be further developed by providing videos so that education is more effective.